2022
DOI: 10.1057/s41599-022-01457-1
|View full text |Cite
|
Sign up to set email alerts
|

Topical and emotional expressions regarding extreme weather disasters on social media: a comparison of posts from official media and the public

Abstract: Understanding media frames and the public resonance during disasters is essential for making inclusive climate change and adaptation policies in the context of increasingly extreme weather events. In this study, we use the extreme weather and flood event that occurred in July 2021 in Zhengzhou, China, as a case study to investigate how official media in China reported this event and how the public responded. Moreover, since one accountability investigation report regarding this disaster was released in January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Prolonged financial stress due to job loss, mask costs, and the distrust of governmental policies may also contribute to the emergence of pandemic fatigue in the studied period. Fourth, the risk perception is represented in this study by the proportion of weekly surveyed residents who are beyond moderately worried, while in reality, it is a complex concept involving many emotions-including anxiety, depression, post-traumatic stress disorder, and psychological stress triggered by extreme events (e.g., COVID-19, weather disasters) (25)(26). Importantly, excepting worry, other sentiments related to risk perception may have different temporal dynamics and attributes.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged financial stress due to job loss, mask costs, and the distrust of governmental policies may also contribute to the emergence of pandemic fatigue in the studied period. Fourth, the risk perception is represented in this study by the proportion of weekly surveyed residents who are beyond moderately worried, while in reality, it is a complex concept involving many emotions-including anxiety, depression, post-traumatic stress disorder, and psychological stress triggered by extreme events (e.g., COVID-19, weather disasters) (25)(26). Importantly, excepting worry, other sentiments related to risk perception may have different temporal dynamics and attributes.…”
Section: Discussionmentioning
confidence: 99%
“…Using social media data to monitor public emotional well-being and psychological responses to climate change Numerous studies have demonstrated social media's potential to understand the public's perception and emotional responses to climate change-related events [51][52][53] . Through the use of natural language processing and network analysis, researchers have been able to study public reactions and sentiments to climate policy actions on social media platforms such as X (formally known as Twitter) 54 .…”
Section: Somatosensory Experiencesmentioning
confidence: 99%
“…In September 2023, the monthly active users reached 605 million, and the average daily active users were 260 million 64 . In addition, Weibo has been widely used to investigate climate change discourses 65 and impacts 12,51 . Guided by the climate response-related theories as our theoretical foundation, we propose and test one novel mechanism between meteorological indicators and emotional responses through three cognitive pathways (Figure 1).…”
Section: Somatosensory Experiencesmentioning
confidence: 99%
“…Official media reflects its own attention distribution—as evidenced by analyses of the intensity, emotion, and content of reports—and of the policymakers, as conveyed by the selection and dissemination of topics guiding public opinion and discussion. Research has demonstrated that posts from official media and public comments differed by themes [ 6 ]. The media’s framing can affect public opinion and policy debates, with different types of newspapers presenting different frameworks [ 7 ].…”
Section: Introductionmentioning
confidence: 99%